MEMS technology for optical networking applications. - Neukermans, A. (IEEE Communications magazine)
The explosion of the Internet has brought about an acute need for broadband communications, which can only be filled with optical networking. This in turn has resulted in an unprecedented interest in optical micro-electromechanical systems. Since the early days of fiber optics, it has been recognized that micro-optics was a fertile ground for the applications of MEMS. MEMS-based products offer substantial cost and performance advantages for optical networking applications in the area of switching fabrics, variable attenuators, tunable lasers, and other devices. This article provides a review of various types of MEMS technologies for optical networking applications